2014
DOI: 10.1055/s-0033-1360300
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Effect of Scutellaria baicalensis Extract and Its Active Compound, Baicalin, on the Translocation of the Androgen Receptor with Implications for Preventing Androgenetic Alopecia

Abstract: Androgens affect several human skin and prostate functions, and the androgen receptor is crucial for regulating the androgen-related mechanisms. In this study, we assessed the antagonizing effects of a Scutellaria baicalensis extract and its main component baicalin on proliferation of human scalp dermal papilla cells. First, the extract and baicalin slightly dissociated the radioisotope-labeled androgen receptor-agonist complex in the androgen receptor binding assay, and the IC50 values were measured to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 15 publications
(17 reference statements)
2
26
0
Order By: Relevance
“…[1][2][3] In recent years, a large number of pharmacological studies have shown that flavonoids were the main active constituents in S. baicalensis. [3][4][5] At present, more than 60 flavonoids have been isolated from S. baicalensis and identified.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] In recent years, a large number of pharmacological studies have shown that flavonoids were the main active constituents in S. baicalensis. [3][4][5] At present, more than 60 flavonoids have been isolated from S. baicalensis and identified.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, researchers have been exploring various promoting agents for SCs proliferation, such as interleukin-1β (14) and tanshinone IIA (15 Utilizing plant-derived traditional Chinese medicines to treat various types of diseases has a long history in East Asian countries, such as China, Korea and Japan (16). Furthermore, some western medicines are derived from major constituent of traditional Chinese medicine (17) Scutellaria baicalensis Georgi (Huangqin in Chinese), a traditional Chinese medicine, has been used to treat inflammation, fever, ulcers and cancer for hundreds of years (18)(19)(20) and a recent study has reported that flavonoids from the stems and leaves of S. baicalensis Georgi have neuroprotective effects (21). Baicalin, one of the major flavonoid isolated from the root of S. baicalensis, has a variety of biological functions, including anti-inflammatory, anti-oxidant and anti-apoptotic activities (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…It has many pharmaceutical actions such as anti-inflammatory action, antibiotic action, antioxidant properties, and antiproliferative effects on prostate cancer cells. Further, Baicalin antagonises the androgen receptor by suppressing the dihydrotestosterone dependent activation cascade and also promotes proliferation of the human papillary dermal cells [5]. Baicalin activates Wnt/βcatenin signaling in a dose dependent manner in human dermal papilla cells.…”
Section: Discussionmentioning
confidence: 95%